Análise comparativa do módulo de elasticidade calculado segundo diferentes normas - Cabral, Larissa Marques Cunha (2014)
The work involved studying the behavior and adjustment of dosage diagram of concrete with respect to static and dynamic elastic modulus. Furthermore, it compares the models of the static elastic modulus based on the compressive strength, German, European, American and Brazilian ABNT NBR 6118 (2014) prediction - Design of Concrete Structures: procedure. Two concrete were produced with different consistency; plastic and other fluid (selfcompacting). Three traits were developed for each consistency, totaling six traits. These dosages were as varying the water / cement and cement consumption; the rebate was kept constant. A comparative analysis of the experimental results with those predicted by some standards was carried out to evaluate the level of accuracy of the same. ACI 318 (2014) was the standard that had their closest results compared to NBR 6118 (2014). Have the Eurocode and DIN 1045 standards -2 showed similar results. And the standard fib CEB - 2010, showed overestimated values in relation to other standards. Thus, we can say that the determination of elasticity of the concrete module proved consistent with the materials and dosages used. However, it is very sensitive to the composition of the trace variable, even when kept the materials. The compressive strength is one of the variables that affect the results. However, it also has great influence to change the nature of the coarse aggregate and the relative folder / coarse aggregate, for example. The dynamic ultrasonic waves through the module was also measured and compared with the static module, showing a rapid and non-destructive option to evaluate the modulus of elasticity of the concrete.